Influence of soil physico-chemical properties on productivity of black pepper (Piper nigrum L.) - Srinivasan, S Hamza, A K Sadanandan, V (Journal of Spices and Aromatic Crops, 2004)
Soil surveys were conducted to study the physico-chemical characteristics of major black pepper (Piper nigrum) growing soils in Kerala and their relationship with black pepper productivity. Soil samples were collected from four major black pepper growing districts, namely, ldukki, Wayanad (high elevation), Kozhikode and Kannur (low elevation) and were classified based on yield as high, moderate and low yieJdinggardens. The relationships between elevations, physico-chemical properties and black pepper productivity were studied. The investigation revealed that soils of high yielding gardens were high in sand and low in clay fractions. These soils had high pH, base saturation, canon exchange capacity, organic carbon, phosphorus, potassium, calcium, magnesium and zinc status compared to low yielding gardens. These factors favoured good growth of black pepper vines with higher productivity.